KARATERISTIK TEPUNG KEDELAI DARI JENIS IMPOR DAN LOKAL (VARIETAS ANJASMORO DAN BALURAN) DENGAN PERLAKUAN PEREBUSAN DAN TANPA PEREBUSAN - Muhammad Gozalli; Nurhayati Nurhayati; Ahmad Nafi' (JURNAL AGROTEKNOLOGI, 2015)
Soybean is the raw material that has a high protein. Indonesian soybean consumption per capita increased from 8.13 kg in 1998 to 8.97 kg in 2004. Soybean flour is the intermediete food. Soybean flour in the market was not yet known the certain nutritional content because of different soybean varieties. Two the best Jember varieties of soybean are Anjasmoro and Baluran. Imported soybean also has different characteristics that will affect the characteristics of the flour. This study used completely randomized design (CRD) with two factors: the type of soybean (Anjamoro/A1, Baluran/A2, and Import/A3) and treatment of flouring (Blanching/B1 and Non-Blanching/B3). The parameters observed were the brightness, yield and chemical properties include the levels of content soluble protein and content proximate. The results showed that the soybean flour in blanching and non-blanching process of imported and local soybean (Anjasmoro and Baluran) had non-significant effect on the level of yield, brightness, protein content, fat content, moisture content and carbohydrate content, but significant effect on the level of content soluble protein and ash content.Keywords: soybean, treatment flouring, soybean flour